PAKET SOFTWARE UNTUK SIMULASI GERBANG LOGIKA DASAR - Bunyamin Bunyamin (Jurnal Elektronika Telekomunikasi & Computer, 2016)
Object of the research is to create a software that can simulate work principle of the basic logic gate. Research using the analysis method of analyzing a number of requirements and design a simulation object model of object-oriented programs. The result of this study is a software package that can simulate work principle of the basic logic methodKey Words : software, basic logic gate, object oriented